Persistence of Lymphocystis Disease Virus (LCDV) in Seawater - Leiva Rebollo, Rocío; Labella Vera, Alejandro Manuel; Jiménez Valverde, Estefanía; Castro-López, María Dolores; Borrego-García, Juan José (Springer Link, 2020)
Lymphocystis disease virus (LCDV), the causative agent of lymphocystis disease (LCD), is a waterborne pathogen that uses the external surfaces, including the gills, as portals to gain access to fsh host. However, there are no data on LCDV persistence in the aquatic environment. In this study, the persistence of LCDV in natural (raw), treated (autoclaved and fltered) and synthetic seawater held at 22 and 18 °C has been evaluated. The estimated T99 values for LCDV in seawater ranged from 2.7 to 242 days depending on seawater type and temperature, with the highest value recorded at 22 °C in autoclaved seawater. Microbiota and temperature seem to be the main factors afecting the persistence of LCDV in seawater. The results indicated that LCDV is more stable in treated seawater than most of the fsh pathogenic viruses studied so far, supporting the relevance of this medium for the prevalence of LCD in fsh farms.
Keywords: Peces - Enfermedades por virus; Lymphocystis disease virus; Persistence; Seawater; Temperature; Microbiota; Abiotic factors